From cyanobacteria to Archaeplastida: new evolutionary insights into PII signalling in the plant kingdom. Issue 3 (27th March 2020) - Selim, Khaled A.; Ermilova, Elena; Forchhammer, Karl
Summary: The PII superfamily consists of signal transduction proteins found in all domains of life. Canonical PII proteins sense the cellular energy state through the competitive binding of ATP and ADP, and carbon/nitrogen balance through 2‐oxoglutarate binding. The ancestor of Archaeplastida inherited its PII signal transduction protein from an ancestral cyanobacterial endosymbiont. Over the course of evolution, plant PII proteins acquired a glutamine‐sensing C‐terminal extension, subsequently present in all Chloroplastida PII proteins. The PII proteins of various algal strains (red, green and nonphotosynthetic algae) have been systematically investigated with respect to their sensory and regulatory properties. Comparisons of the PII proteins from different phyla of oxygenic phototrophs (cyanobacteria, red algae, Chlorophyta and higher plants) have yielded insights into their evolutionary conservation vs adaptive properties. The highly conserved role of the controlling enzyme of arginine biosynthesis, N ‐acetyl‐l ‐glutamate kinase (NAGK), as a main PII‐interactor has been demonstrated across oxygenic phototrophs of cyanobacteria and Archaeplastida. In addition, the PII signalling system of red algae has been identified as an evolutionary intermediate between that of Cyanobacteria and Chloroplastida. In this review, we consider recent advances in understanding metabolic signalling by PII proteins of the plant kingdom.